Pelatihan Tableau Untuk Visualisasi Data Secara Cepat dan Mudah - FRANSISCA, DIANDRA CHIKA; Raharja, Pradana Ananda (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2024)
Human consumption of data and information has become very large due to the enormous growth of data. On the other hand, the increasing need for data visualization in various information media (online or offline) has also become very interesting. Data visualization is not only about beautifying the appearance of data but also about making data more quickly understood and engaging. Tableau specializes in data visualization, data storytelling and dashboards. Training to operate Tableau can answer the needs of pupils, students, the general public, teachers and lecturers as participants. This training aims for participants to apply interactive data visualization quickly and easily using Tableau in dashboard creation activities to explain data in visual form. The methods used in implementing this training are preparation methods and implementation methods as well as training. As a result of this training, 34 participants learned about the importance of data visualization. They learned Tableau as a data visualization tool and visualization training using Tableau to create self-ordered dashboards for examples of COVID-19 cases worldwide.